Membangun Koperasi Didalam Sistem Ekonomi Pasar - Ariffin, Ramudi (Koaliansi : Cooperative Journal, 2021)
On the one hand, it is believed that economic problems are material problems and therefore the basis of economic power is aninvestment which leads to capital (material) variables. On the other hand, they assume that the economic problem is a matter of human life and therefore the basis of economic power is the human being himself. In this case, the following explanation can be simplified to three main points, namely the market economy system, the economic system of cooperatives and cooperatives. Companies that have succeeded in a market economy system, continue to reinvest the accumulated business profits they have achieved. Then is it necessary to avoid a market economy system, Cooperative Companies are not a form of capital accumulation but the accumulation of interests or economic activities that are integrated into one group organization. The key to the strength of the Cooperative is the building of a commitment from everyone in it to always be disciplined in carrying out organizational norms and obeying in carrying out operational decisions that have been mutually agreed upon, including sanctions against those who violate it.